Desenvolvimento e caracterização de um sistema de liberação transdérmica de substância química hidrofílica com potencial vasodilatador para tratamento da alopécia - Camila Monteiro Cruz (2018)
Alopecia is a disease characterized by hair loss, whosepathophysiology can be related to hormonal metabolism of androgens or autoimmunity, being called androgenetic or areata alopecia, respectively. The drug treatments previously described have been effective in capillary growth induction. However, continuous use is required, and the symptoms tend to recur if the treatment is discontinued, and treatment is commonly discontinued because of serious adverse effects. In this work, a transdermal gel-cream containing a vasodilating chemical substance was formulated and characterized. The pharmacological re-adaptation proposed herein may be a new alternative to provide a more effective treatment option for patients. The physico-chemical characterization included determination of pH, cremation, density, viscosity, spreadability, as well as dosing and in vitro release profile tested by a validated method. A slightly acidic pH was found, which is compatible with the application on the skin, and the rheological profile was adequate for the proposed storage and use conditions. The release profile demonstrates the capacity of the delivery system to liberate about 90% of the active compound over a period of approximately 10 hours with a suitable release rate for a local effect.